The relationship of preoperative estimated glomerular filtration rate and outcomes after cardiovascular surgery in patients with normal serum creatinine: a retrospective cohort study - Myung-Soo Jang; Jae-Sik Nam; Jun-Young Jo; Chang-Hwa Kang; Seung Ah. Ryu; Eun-Ho Lee; In-Cheol Choi (BMC Anesthesiology, 2019)
Abstract Background Although serum creatinine concentration has been traditionally used as an index of renal function in clinical practice, it is considered relatively inaccurate, especially in patients with mild renal dysfunction. This study investigated the usefulness of preoperative estimated glomerular filtration rate (eGFR) in predicting complications after cardiovascular surgery in patients with normal serum creatinine concentrations. Methods This study included 2208 adults undergoing elective cardiovascular surgery. Preoperative eGFR was calculated using Chronic Kidney Disease Epidemiology Collaboration equations. The relationships between preoperative eGFR and 90 day postoperative composite major complications were analyzed, including 90 day all-cause mortality, major adverse cardiac and cerebrovascular events, severe acute kidney injury, respiratory and gastrointestinal complications, wound infection, sepsis, and multi-organ failure. Results Of the 2208 included patients, 185 (8.4%) had preoperative eGFR < 60 mL/min/1.73 m2 and 328 (14.9%) experienced postoperative major complications. Multivariable logistic regression analyses showed that preoperatively decreased eGFR was independently associated with an increased risk of composite 90 day major postoperative complications (adjusted odds ratio: 1.232; 95% confidence interval [CI]: 1.148–1.322; P <  0.001). eGFR was a better discriminator of composite 90 day major postoperative complications than serum creatinine, with estimated c-statistics of 0.724 (95% CI: 0.694–0.754) for eGFR and 0.712 (95% CI: 0.680–0.744) for serum creatinine (P = 0.008). Conclusions Decreased eGFR was significantly associated with an increased risk of major complications after cardiovascular surgery in patients with preoperatively normal serum creatinine concentrations.